ISO 14001 sistema de gestión ambiental (2016)
The set of actions in pursuit of maximum rationality in the decision process concerning the conservation, defense, protection and improvement of the environment, based on coordinated multidisciplinary information and citizen participation is known as environmental management. This article is to conduct an analysis of Environmental Management Systems (EMS) and understand the purpose that provides organizations with the aim to understand the advantages and disadvantages that come from implementing an EMS in an organization. In carrying out the article conducted a literature search for documentary information concerning the SGA. The identification of the legal and environmental aspects are the basis on which the EMS structure, since these originate from the objectives, goals, programs, and in general all elements of the organization. From a global perspective,the emplementation of international environmental management standards that promote care of the environment (air, water and soil quality), represent a major contribution to global efforts to conserve the environment in which we live.